Creolized Sexualities : Undoing Heteronormativity in the Literary Imagination of the Anglo-Caribbean - Donnell, Alison, 1966- (Critical Caribbean studies., 2021)
Creolized Sexualities: Undoing Heteronormativity in the Literary Imagination of the Anglo-Caribbean draws attention to a wide, and surprising, range of writings that craft inclusive and pluralizing representations of sexual possibilities within the Caribbean imagination. Reading across an eclectic range of writings from V.S. Naipaul to Marlon James, Shani Mootoo to Junot Diaz, Andrew Salkey to Thomas Glave, Curdella Forbes to Colin Robinson, this bold work of literary criticism brings into view fictional worlds where Caribbeanness and queerness correspond and reconcile. Through inspired close readings Donnell gathers evidence and argument for the Caribbean as an exemplary creolized ecology of fluid possibilities that can illuminate the prospect of a non-heteronormalizing future. Indeed, Creolized Sexualities hows how writers have long rendered sexual plasticity, indeterminacy, and pluralism as an integral part of Caribbeanness and as one of the most compelling if unacknowledged ways of resisting the disciplining regimes of colonial and neocolonial power.